Elaboración de una galleta a base de glicerina y clorofila líquida para el cuidado dental en caninos (canis lupus familiares) en el barrio San José del Condado - Araque Barrionuevo, Cynthia Domenica (2021)
The general health of canines is affected greatly according to their oral health and their eating habits, due to the time availability and the high costs of some treatments, biscuits were made to prevent periodontal diseases being this an easiest practice as well as inexpensive. The objective of this study was to evaluate the efficacy of glycerin and liquid chlorophyll through the use of biscuits to prevent periodontal diseases in canines. 20 domestic canines of different race, sex, that had a mixed diet and an age between 1 to 3 years were evaluated, which presented problems of halitosis and gingivitis; the experiment was randomly divided into 2 groups of 10 canines with their respective treatments, a microbiological culture was carried out at the beginning and at the end of the investigation in order to know the bacterial amount in the oral cavity. The results were analyzed by T-student; where it was shown that at the beginning of the control treatment and treatment itself, 1 a 90% were positive and 10% negative for CFU; as a response in treatment 1, a decrease in CFU was demonstrated on day 30, while the control treatment had an increase of 100%. However, a statistically significant relationship was observed between treatment 1 and the variables associated with it, where the decrease in CFU, halitosis and gingivitis was demonstrated, considering that the p-value in each of these variables was lower than the level of significance with what has been worked (0.05). Keywords: periodontal